URBAN RESIDENTIAL DENSITY AND OPEN DEFECATION IN OSOGBO, OSUN STATE, NIGERIA - OLAYODE, Olayiwola; ADEDOTUN, David Oluwatoyin; OLAYODE, Chritiana (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2025)
The study examines the relationship between urban residential density and open defecation in Osogbo to provide a comprehensive database to develop guidelines for policy making. Primary and secondary data sources were used to investigate information on the number of toilets available, places used for open defecation, and reasons for open defecation. A multi-stage sampling approach was adopted, which included stratification of Osogbo into three (3) residential density areas, followed by random selection of respondents in each sampled density. Due to population variation of the residential density areas selected a proportionate sampling technique was used in selecting a sample size of 240 respondents using a ratio of 1:2:3.Differences in observations were tested with the Chi-square statistical technique, while the mean value was used to determine respondents’ reasons and places used for open defecation in the study area. Precisely, 54.2% of respondents were involved in open defecation in the high residential density areas, while 50% were involved in the low residential density areas. As high as 62.5% of respondents used open space for defecation in the medium residential density areas, while 50% and 37.5% of respondents used the same in the high and low residential density areas. Absence of toilet facility ranked as the highest reason for open defecation across the 3 residential density areas, with 58.3%, 43.7%, and 62.5% respondents in the high, medium, and low residential density areas. Multiple Analysis of Variance (MANOVA) shows that residential density has no significant relationship with the incidence of open defecation in the study area, with a P-value of .0670.There is a need for a vigorous campaign on the health implications of open defecation on the residents’ quality of life and the environment in general.